A lignin flame retardant and its preparation method and flame retardant composite material
By grafting phosphate groups on the surface of lignin and forming an ammonium polyphosphate structure, the problems of low flame retardant efficiency and organic solvent pollution are solved, and efficient flame retardant performance and mechanical properties are achieved.
Patent Information
- Application Number
- CN202310725866.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-19
AI Technical Summary
In the prior art, lignin has low flame retardant efficiency and needs to be physically blended with ammonium polyphosphate flame retardant, resulting in large amount of flame retardant added, affecting the mechanical properties of polymer matrix, and is often used in research on modified lignin. Organic solvents lead to environmental pollution problems.
By grafting phosphate groups on the surface of lignin and using in situ polymerization and condensation reaction, lignin flame retardant containing ammonium polyphosphate structure is prepared, and lignin is phosphated under organic solvent conditions using the hydroxyl active site of lignin. The formation of phosphate groups with high grafting rate improves flame retardant properties.
A better flame retardant effect and lower flame retardant addition amount are achieved, while avoiding the use of organic solvents, reducing environmental pollution, and maintaining the mechanical properties of the material.
Smart Images

Figure CN116715867B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant materials and relates to a lignin flame retardant and a preparation method thereof and a flame retardant composite material. Background Art
[0002] Lignin is the most abundant aromatic polymer in nature. The pulp and paper industry produces 50 million tons of lignin waste each year, only a small part of which is used. If this lignin is used, it will contribute to economic and environmental sustainability.
[0003] Lignin contains many phenol structures in its three-dimensional structure and has good carbon-forming ability. It is a good bio-based material for reducing the flammability of polymer materials. Moreover, lignin has a variety of functional groups, such as methoxy, alcohol hydroxyl, phenolic hydroxyl, ethyl, phenyl, aldehyde, carbonyl, etc., which provide abundant active sites for further chemical modification. Therefore, many scholars have studied lignin and its derivatives as flame retardants. However, the current technology still has the following problems: (1) The flame retardant efficiency of lignin is very low, and it needs to be physically blended with ammonium polyphosphate flame retardants to have a good flame retardant effect. At the same time, the amount of flame retardant added is large, which will deteriorate the mechanical properties of the polymer matrix; (2) In the research on modified lignin, most of them need to use organic solvents, which easily lead to VOCs (volatile organic compounds) environmental problems. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems in the prior art and to provide a lignin flame retardant including an ammonium polyphosphate structure, wherein the phosphate groups with a high grafting rate ensure the flame retardant performance.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing a lignin flame retardant, the preparation method comprising:
[0007] S1, dissolving lignin, urea and a phosphorus source in water to prepare a mixed solution, heating and stirring the solution, drying, and heating and curing the solution for a second time to graft phosphoric acid groups on the surface of the lignin to obtain phosphorylated lignin;
[0008] S2, mixing the phosphorylated lignin, phosphorus source and nitrogen source in S1, heating and stirring for reaction, and heating and curing for a second time to obtain a lignin flame retardant containing an ammonium polyphosphate structure.
[0009] The invention grafts phosphoric acid groups on the surface of lignin through phosphorylation, and then obtains a lignin flame retardant containing an ammonium polyphosphate structure through an in-situ polymerization condensation reaction.
[0010] Preferably, the lignin content in the mixed solution in step S1 is 1-5wt%.
[0011] Preferably, in step S1, the mass ratio of lignin, urea and phosphorus source is 1:(1-5):(1-6).
[0012] More preferably, the mass ratio of urea to phosphorus source is 1:(0.5-6).
[0013] Preferably, in step S1, the temperature of the heating and stirring reaction is 60-90°C for 0.5-3h; the secondary heating and curing temperature is 120-190°C for 0.5-3h.
[0014] Preferably, in step S1, the phosphorus source includes one or more of ammonium hydrogen phosphate, phosphoric acid, and phosphorus pentoxide.
[0015] More preferably, when the phosphorus source is ammonium hydrogen phosphate, the mass ratio of lignin, urea and phosphorus source is 1:(2-3):(1.5-3).
[0016] Preferably, in step S1, the phosphorylated lignin is further soaked in a 1.2-2 mol / L HCl solution for 3-10 hours.
[0017] Preferably, in step S2, the mass ratio of phosphorylated lignin, phosphorus source and nitrogen source is 1:(1-4):(0.3-2.4).
[0018] Preferably, in step S2, the temperature of the heating and stirring reaction is 110-150°C, and the time is 0.1-2h; the secondary heating and curing temperature is 200-300°C, and the time is 0.5-5h.
[0019] Preferably, in step S2, the phosphorus source includes one or more of (concentrated) phosphoric acid and ammonium phosphate, and the nitrogen source includes one or more of urea and ammonia.
[0020] More preferably, when the phosphorus source is phosphoric acid and the nitrogen source is urea, the mass ratio of phosphorylated lignin, the phosphorus source, and the nitrogen source is 1:(1-2):(1-2.4).
[0021] More preferably, when the phosphorus source is ammonium phosphate and the nitrogen source is urea, the mass ratio of phosphorylated lignin, phosphorus source and nitrogen source is 1:(1-4):(0.5-2).
[0022] More preferably, when the phosphorus source is phosphoric acid and the nitrogen source is ammonia, the mass ratio of phosphorylated lignin, phosphorus source, and nitrogen source is 1:(1-2):(0.3-0.6).
[0023] A lignin flame retardant, the lignin flame retardant comprises an ammonium polyphosphate structure; the structure is shown in the following formula (1):
[0024]
[0025] Where R1 is combination; R2 is Both m and n are greater than 1;
[0026] The grafted amount of the phosphoric acid group is 45 to 55 wt %.
[0027] A flame retardant composite material contains 1 to 8 wt% of a lignin flame retardant.
[0028] Preferably, the flame retardant composite material is prepared by melt blending a flame retardant having an ammonium polyphosphate structure with a thermoplastic polymer.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention utilizes the hydroxyl active sites on the surface of lignin, and in the absence of an organic solvent, firstly grafts phosphoric acid groups on the surface of lignin by phosphorylation, and then obtains a lignin flame retardant with an ammonium polyphosphate structure modified by an in-situ polymerization condensation reaction;
[0031] 2. The lignin flame retardant of the present invention includes an ammonium polyphosphate structure, and the amount of phosphoric acid group grafting is 45-55wt%. The more phosphoric acid groups there are, the more acid sources there are in the flame retardant system, which can promote the carbonization process of lignin and generate more protective carbon layers, thereby achieving better flame retardant effect.
[0032] 3. The flame retardant composite material of the present invention contains 1 to 8 wt% of lignin flame retardant, which reduces the amount of flame retardant added while meeting the flame retardant performance requirements and hardly affects the mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a flow chart for preparing the lignin flame retardant in Example 1 of the present invention.
[0034] Figure 2 The infrared spectra of lignin (Lignin), phosphorylated lignin (P-Lig), and ammonium polyphosphate-modified lignin (Lig-APP) in Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0035] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0036] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.
[0037] Example 1
[0038] Preparation of lignin flame retardant including ammonium polyphosphate structure:
[0039] S1. Add 5.0g lignin, 12.0g urea and 11.5g NH4H2PO4 to 180mL deionized water at one time, heat to 70℃ for reaction for 1.0h under magnetic stirring, and then dry to constant weight; transfer to an oven for secondary heating and curing at 170℃ for 1.0h; then soak the cooled solid in 1.5mol / L HCl solution for 4.0h, wash with water by centrifugation, and dry in vacuum at 60℃ for 12h to obtain brown-black phosphorylated lignin (P-Lig);
[0040] S2. Weigh 9.8g of phosphorylated lignin, add 11.5g of H3PO4 concentrated solution (85%) and 12.0g of urea, stir and heat to 120°C and keep for 20min, move to an oven, heat and cure at 230°C for 2.5h, cool to room temperature to obtain a gray solid; then grind in a ball mill at 300rpm / min for 15min, wash with deionized water until the centrifuge is neutral; continue to vacuum dry at 60°C for 12h, grind again in a ball mill at 300rpm for 15min to obtain gray ammonium polyphosphate modified lignin (Lignin modified by APP, Lig-APP) with a grafting amount of 50wt%.
[0041] Figure 1 The following is a flow chart of the preparation in this example, and the infrared spectra of Lignin, P-Lig, and Lig-APP.
[0042] Example 2
[0043] Compared with Example 1, the difference is that the raw materials in step S1 include 5.0 g lignin, 8.0 g urea, and 14.0 g phosphorus pentoxide.
[0044] Example 3
[0045] Compared with Example 1, the difference is that the raw materials in step S1 include 5.0 g lignin, 16.0 g urea, and 10.0 g phosphoric acid.
[0046] Example 4
[0047] Compared with Example 1, the difference is that in step S2, the raw materials include 9.8g of phosphorylated lignin, 16.0g of ammonium phosphate (NH4H2PO4), and 8.0g of urea. The raw materials are placed in a tubular furnace and heated to 120°C for 20 minutes.
[0048] Example 5
[0049] Compared with Example 1, the difference is that in step S2, the raw materials include 9.8g of phosphorylated lignin, 11.5g of phosphoric acid (concentration 85%), and 3.5g of ammonia (4.54L). The solid raw material is placed in a tubular furnace, ammonia is introduced, and the temperature is raised to 120°C and maintained for 20min.
[0050] Example 6
[0051] Compared with Example 1, the difference is that the secondary heating and curing temperature in step S2 is 190°C.
[0052] Comparative Example 1
[0053] Compared with Example 1, the difference is that step S1 is not performed, and lignin is directly added into step S2 instead of phosphorylated lignin.
[0054] Application Example 1
[0055] After polylactic acid (PLA) was vacuum dried at 100°C for 6h, 3wt% of the lignin flame retardant (Lignin modified by APP, Lig-APP) prepared in Example 1 was added and melt-blended in an internal mixer at 180°C for 6min at a speed of 60rpm; the PLA flame-retardant composite material was preheated at 2MPa and 180°C for 5min, then pressurized to 30MPa, maintained at 180°C for 3min, and then molded at 30MPa for 3min at room temperature to form the composite.
[0056] The product was recorded as PLA / 3Lig-APP, and the flame retardant properties and mechanical properties are shown in Table 1.
[0057] Application Example 2
[0058] Compared with Application Example 1, the difference is that the added amount of the lignin flame retardant (Lignin modified by APP, Lig-APP) prepared in Example 1 is 6 wt %.
[0059] The product is recorded as PLA / 6Lig-APP, and the flame retardant properties and mechanical properties are shown in Table 1.
[0060] Application Example 3
[0061] Compared with Application Example 1, the difference is that the added amount of the lignin flame retardant (Lignin modified by APP, Lig-APP) prepared in Example 1 is 10 wt %.
[0062] The product is recorded as PLA / 10Lig-APP, and the flame retardant properties and mechanical properties are shown in Table 1.
[0063] Application Example 4
[0064] Compared with Application Example 1, the difference is that 3 wt% of lignin is added.
[0065] The product is recorded as PLA / 3Lignin. The flame retardant properties and mechanical properties are shown in Table 1.
[0066] Application Example 5
[0067] Compared with Application Example 1, the difference is that 6 wt% of lignin is added.
[0068] The product is recorded as PLA / 6Lignin. The flame retardant properties and mechanical properties are shown in Table 1.
[0069] Application Examples 6 to 10
[0070] Compared with Application Example 1, the difference is that the lignin flame retardant prepared in Examples 2 to 6 is used.
[0071] The flame retardant properties and mechanical properties are shown in Table 1.
[0072] Application Comparative Example 1
[0073] Compared with Application Example 1, the difference is that the lignin flame retardant prepared in Comparative Example 1 is used.
[0074] The flame retardant properties and mechanical properties are shown in Table 1.
[0075] Table 1. Performance of flame retardant composite materials
[0076] LOI(%) UL-94 Tensile strength(Mpa) National Standard GB / T 2406 GB / T 2408 GB / T 1040 PLA 24.7 V-2 41.1 Application Example 1 27.6 V-0 45.5 Application Example 2 29.4 V-0 40.7 Application Example 3 32.1 V-0 38.2 Application Example 4 23.5 V-2 38.1 Application Example 5 18.6 No level 36.3 Application Example 6 27.3 V-0 44.9 Application Example 7 27.1 V-0 42.7 Application Example 8 26.4 V-0 42.9 Application Example 9 27.5 V-0 43.2 Application Example 10 23.2 V-2 39.9 Application Comparative Example 1 19.8 No level 38.7
[0077] Limiting Oxygen Index LOI (%): The minimum oxygen concentration required for a material to just remain in a combustion state in a specific oxygen and nitrogen mixed gas flow. The higher the value, the better the flame retardant effect.
[0078] According to the above table, in Application Examples 1 to 2 and 6 to 9, the composite materials prepared using different raw materials have good flame retardant properties and mechanical properties; with the increase in the amount of lignin flame retardant added, the limiting oxygen index first increases and then decreases; in Application Examples 1 to 3, the limiting oxygen index gradually increases; in Application Examples 4 to 5, only lignin is added, and with the increase in the amount of lignin added, the flame retardant properties decrease, and the mechanical properties are affected; the composite materials prepared from different raw materials in Application Examples 6 to 9 have improved flame retardant properties and mechanical properties compared to PLA; in Application Example 10, the lignin flame retardant in Example 6 is used, and due to the low curing temperature, the ammonium polyphosphate chain growth reaction cannot be carried out, affecting the flame retardant properties and mechanical properties; in the flame retardant used in Comparative Example 1, the lignin is not phosphorylated, resulting in unsuccessful grafting of ammonium polyphosphate, affecting the flame retardant properties and mechanical properties.
[0079] according to Figure 2 It can be seen that lignin is at 2930cm -1 The stretching vibration of CH is at 1560cm -1 The absorption peak corresponding to C=O is 1260 cm -1 and 1200cm -1 The peak corresponding to the stretching vibration of CO in eugenol and guaiacyl groups is 1035 cm -1 Corresponding to the CO absorption in the methoxy group, 1370 cm -1 Corresponding to the absorption of phenolic hydroxyl groups; after phosphorylation, the infrared absorption peak of the lignin structure did not change much, indicating that the structure of lignin was not destroyed. -1 、1084cm -1 and 1129cm -1 New absorption peaks belonging to P-OH, PO and POC appeared at 477 cm-1, indicating the successful preparation of phosphorylated lignin; Lig-APP showed a strong absorption peak at 477 cm-1. -1 、1089cm -1 and 1438cm -1 The absorption bands at 1257 cm -1 The characteristic peak at 3250cm is attributed to PO3 in ammonium polyphosphate. -1 The vibration peak of the hydroxyl group on the surface of nearby ammonium polyphosphate is further enhanced; at the same time, the lignin 1035cm -1 Other absorption peaks such as CO still exist; these all indicate the successful synthesis of Lig-APP.
[0080] In summary, the present invention utilizes the hydroxyl active sites on the surface of lignin, and in the absence of an organic solvent, first grafts phosphate groups on the surface of lignin by phosphorylation, and then obtains an ammonium polyphosphate structure-modified lignin flame retardant through an in-situ polymerization condensation reaction; the composite material containing the lignin flame retardant meets the flame retardant performance requirements and does not affect the mechanical properties.
[0081] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A method for preparing a lignin flame retardant, characterized in that: The preparation method comprises: S1. Dissolve lignin, urea and a phosphorus source in a mass ratio of 1:(1-5):(1-6) in water to prepare a mixed solution, perform a heating and stirring reaction, dry, and perform a secondary heating and curing to graft phosphoric acid groups on the surface of lignin to obtain phosphorylated lignin; The phosphorus source includes one or more of ammonium hydrogen phosphate, phosphoric acid, and phosphorus pentoxide; The heating and stirring reaction temperature is 60-90°C and the time is 0.5-3h; the secondary heating and curing temperature is 120-190°C and the time is 0.5-3h; S2, mixing the phosphorylated lignin in S1 with a phosphorus source and a nitrogen source, heating and stirring for reaction, and heating and curing for a second time to obtain a lignin flame retardant containing an ammonium polyphosphate structure; The mass ratio of the phosphorylated lignin, the phosphorus source, and the nitrogen source is 1:(1-4):(0.3-2.4); The phosphorus source includes one or more of phosphoric acid and ammonium phosphate, and the nitrogen source includes one or more of urea and ammonia; The temperature of the heating and stirring reaction is 110-150° C., and the time is 0.1-2 hours; the secondary heating and curing temperature is 200-300° C., and the time is 0.5-5 hours.
2. The method for preparing the lignin flame retardant according to claim 1, characterized in that: In the step S1, the phosphorylated lignin is soaked in a 1.2-2 mol / L HCl solution for 3-10 h.
3. The method for preparing the lignin flame retardant according to claim 1, characterized in that: In step S2, when the phosphorus source is phosphoric acid and the nitrogen source is urea, the mass ratio of phosphorylated lignin, the phosphorus source, and the nitrogen source is 1:(1-2):(1-2.4).
4. The method for preparing the lignin flame retardant according to claim 1, characterized in that: In step S2, when the phosphorus source is ammonium phosphate and the nitrogen source is urea, the mass ratio of phosphorylated lignin, phosphorus source and nitrogen source is 1:(1-4):(0.5-2).
5. The method for preparing the lignin flame retardant according to claim 1, characterized in that: In step S2, when the phosphorus source is phosphoric acid and the nitrogen source is ammonia, the mass ratio of phosphorylated lignin, the phosphorus source, and the nitrogen source is 1:(1-2):(0.3-0.6).
6. A lignin flame retardant, characterized in that: The lignin flame retardant is prepared by the preparation method according to any one of claims 1 to 5.
7. The lignin flame retardant according to claim 6, characterized in that The lignin flame retardant includes an ammonium polyphosphate structure; the structure is shown in the following formula (1): Formula (1), Where R1 is , and combination; R2 is ; m and n are both greater than 1; The grafted amount of the phosphoric acid group is 45-55 wt %.
8. A flame retardant composite material, characterized in that: The flame retardant composite material contains 1 to 8 wt % of the lignin flame retardant according to claim 6 or 7.
Citation Information
Patent Citations
Preparation method and application of lignin-based intumescent flame retardant
CN104371116A
Modified lignin flame retardant and preparation method thereof
CN108659228A
